2019
DOI: 10.1007/s10856-019-6232-z
|View full text |Cite
|
Sign up to set email alerts
|

Tethering QK peptide to enhance angiogenesis in elastin-like recombinamer (ELR) hydrogels

Abstract: 6232-z ". "Esta es una preimpresión de un artículo publicado en Journal of Materials Science Materials in Medicine. La versión final autenticada está disponible en línea en:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…30,31 Next to functionalization with adhesion peptides, combinations with growth factor-mimetic sequences additionally promote endothelialization. 32 However, approaches implementing peptide-mediated and affinity-based incorporation of heparin and cytokines in combination with short adhesion peptides have only been exploited in form of hydrogels so far. 33 In the present study, a mussel-derived surface coating combining cell-adhesive as well as heparin-binding and subsequent cytokine-delivering properties is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Next to functionalization with adhesion peptides, combinations with growth factor-mimetic sequences additionally promote endothelialization. 32 However, approaches implementing peptide-mediated and affinity-based incorporation of heparin and cytokines in combination with short adhesion peptides have only been exploited in form of hydrogels so far. 33 In the present study, a mussel-derived surface coating combining cell-adhesive as well as heparin-binding and subsequent cytokine-delivering properties is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is much interest in functionalizing these materials with angiogenic factors (Du, Liu, et al, ; Liekens et al, ; Pensa et al, ). The VEGF‐derived QK peptide is a robust activator of neovascularization, and has therefore been a focus of many tissue regenerative strategies (Cai et al, ; Chan et al, ; Flora, de Torre, Alonso, & Rodriguez‐Cabello, ; Pensa et al, ; Prakash Parthiban, Rana, Jabbari, Benkirane‐Jessel, & Ramalingam, ). In multiple preclinical animal models, the QK peptide and rVEGF have been reported to induce a comparable degree of angiogenesis (Finetti et al, ; Santulli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…John et al (2019) fabricated a GelMA nanofiber microsphere coated with VEGF-mimic peptides, and showed the formation of vascular tubes by HUVEC. Similarly, Flora et al (2019) demonstrated that elastin-like recombinamer (ELR) tethered with VEGFmimic peptides not only improved vascularization in vitro, but also in vivo. In fact, ELR injected into mice enhanced the recruitment and proliferation of ECs, and the number of capillaries (Flora et al, 2019).…”
Section: Promotion Of Cell Adhesionmentioning
confidence: 97%